Usefulness of a Multiplex PCR for Detection of Diarrheagenic Escherichia coli in a Diagnostic Microbiology Laboratory Setting (Bangladesh Journal of Medical Microbiology, 2016)
A multiplex PCR assay was evaluated for diagnosis of diarrheagenic Escherichia coli in stool samples of patients with diarrhoea submitted to a diagnostic microbiology laboratory. Two procedures of DNA template preparationproteinase K buffer method and the boiling method were evaluated to examine isolates of E. coli from 150 selected diarrhoeal cases. By proteinase K buffer method, 119 strains (79.3%) of E. coli were characterized to various categories by their genes that included 55.5% enteroaggregative E. coli (EAEC), 18.5% enterotoxigenic E. coli (ETEC), 1.7% enteropathogenic E. coli (EPEC), and 0.8% Shiga toxin-producing E. coli (STEC). Although boiling method was less time consuming (